2019
DOI: 10.1186/s13046-019-1327-4
|View full text |Cite
|
Sign up to set email alerts
|

RhoC: a fascinating journey from a cytoskeletal organizer to a Cancer stem cell therapeutic target

Abstract: Tumor heterogeneity results in differential response to therapy due to the existence of plastic tumor cells, called cancer stem cells (CSCs), which exhibit the property of resistance to therapy, invasion and metastasis. These cells have a distinct, signaling network active at every stage of progression. It is difficult to envisage that the CSCs will have a unique set of signaling pathways regulating every stage of disease progression. Rather, it would be easier to believe that a single pivotal pathway having s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 99 publications
(109 reference statements)
1
38
0
Order By: Relevance
“…RhoC is a guanosine triphosphatase that can modulate the proliferation, differentiation, and apoptosis of normal cells [21][22][23] . Previous studies have shown that the Rhofamily of small GTPases has an essential role in transmitting the VEGF signals downstream to angiogenesis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…RhoC is a guanosine triphosphatase that can modulate the proliferation, differentiation, and apoptosis of normal cells [21][22][23] . Previous studies have shown that the Rhofamily of small GTPases has an essential role in transmitting the VEGF signals downstream to angiogenesis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…RhoC (Ras homolog gene family member C) regulates cytoskeletal organization and affects the motility of cancer cells favoring invasion and metastasis as well as progression and VM formation (74). In hepatocellular carcinoma (HCC), vascular channels were formed, and these vessels were associated with RhoC FAK/Paxillin signaling regulation as well as with high expression of RhoC/ROCK2, VE-cadherin, and MMP2 mediated by ERK/MMPs signaling (75).…”
Section: Mechanisms Of Vm In Human Cancersmentioning
confidence: 99%
“…Our work on the role of RhoC in tumor progression along with other abundant literature, support the contribution of RhoC in determining the sequence of events during tumor progression. Beginning from tumor formation till metastasis, RhoC is required for all the intervening steps, which include invasion, anoikis resistance, intravasation, extravasation and homing (Reymond et al, 2015; Srivastava et al, 2010; Thomas, Pranatharthi, Ross, & Srivastava, 2019). We have recently observed that RhoC provides radioprotection to tumor cells, a hallmark of cancer stem cells (Pranatharthi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly the regulation of metastasis by RhoC has been well elaborated in several tumors (Clark, Golub, Lander, & Hynes, 2000; Hakem et al, 2005; Hoshino, Koshikawa, & Seiki, 2010; Iiizumi et al, 2008; Islam, Sharma, Kumar, & Teknos, 2013; Kleer et al, 2006; Kleer et al, 2002; Rosenthal et al, ; Wu, Wu, Kumar-Sinha, Chinnaiyan, & Merajver, 2004; Xing et al, ; Yao, Dashner, van Golen, & van Golen, 2006), where they show that alteration in the expression of RhoC results in changes in metastasis. Similarly, its role in regulating angiogenesis, anoikis resistance and cancer stem cell maintenance is undisputable (Thomas et al, 2019). The role of Notch1 in regulating RhoC in cervical cancer illustrates its upstream regulatory mechanism (Srivastava et al, 2010) as there is no driver mutation observed in RhoC as per the TCGA data, 2019.…”
Section: Introductionmentioning
confidence: 99%